2015
DOI: 10.3109/09593985.2015.1027070
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of shoulder active range of motion in prone versus supine: a reliability and concurrent validity study

Abstract: Climstein, M. (2015). Assessment of shoulder active range of motion in prone versus supine: a reliability and concurrent validity study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
3
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 17 publications
0
20
3
4
Order By: Relevance
“…The intra-examiner values in this study (>0.80) for both internal and external rotation were superior to some (Awan, Smith, & Boon, 2002;Walker, et al, 2016) but slightly lower than others that have reported ICC values of greater than 0.9 (Cools, et al, 2014;Furness, et al, 2015) using an inclinometer. The good to excellent reliability values found for inter-examiner assessment are similar to previous studies that have also found good to excellent reliability values both in swimmers (Riemann, et al, 2011;Walker, et al, 2016) and non-swimmers (Cools, et al, 2014;Furness, et al, 2015). The generally low levels of SEM in this study indicate consistency across testing sessions and between examiners for this test battery and compare favorably to previous reliability studies that have reported SEM values of 2-5° for active shoulder movements (Kolber, Vega Jr, Widmayer, & Cheng, 2011;Walker, et al, 2016).…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…The intra-examiner values in this study (>0.80) for both internal and external rotation were superior to some (Awan, Smith, & Boon, 2002;Walker, et al, 2016) but slightly lower than others that have reported ICC values of greater than 0.9 (Cools, et al, 2014;Furness, et al, 2015) using an inclinometer. The good to excellent reliability values found for inter-examiner assessment are similar to previous studies that have also found good to excellent reliability values both in swimmers (Riemann, et al, 2011;Walker, et al, 2016) and non-swimmers (Cools, et al, 2014;Furness, et al, 2015). The generally low levels of SEM in this study indicate consistency across testing sessions and between examiners for this test battery and compare favorably to previous reliability studies that have reported SEM values of 2-5° for active shoulder movements (Kolber, Vega Jr, Widmayer, & Cheng, 2011;Walker, et al, 2016).…”
Section: Discussioncontrasting
confidence: 74%
“…When comparing our results to previous ROM reliability studies only a few measures can be accurately scrutinized, as although some of the tests within this battery are used routinely within swimming screenings and clinical assessments (Blanch, 2004), there is a paucity of literature examining their reliability. Shoulder internal rotation and external rotation are two exceptions as they are measures that have received repeated attention within the literature (Cools, et al, 2014;Furness, Johnstone, Hing, Abbott, & Climstein, 2015;Riemann, Witt, & Davies, 2011;Walker, et al, 2016). The intra-examiner values in this study (>0.80) for both internal and external rotation were superior to some (Awan, Smith, & Boon, 2002;Walker, et al, 2016) but slightly lower than others that have reported ICC values of greater than 0.9 (Cools, et al, 2014;Furness, et al, 2015) using an inclinometer.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…12,15,31 In the present study, a digital goniometer was used (HALO Medical Devices), combined with a universal goniometer with prolonged arms to measure ROM. 8,11,12,15 A few times, when held horizontally, the digital goniometer was shown to measure angles higher than the universal goniometer. The measurements of hip internal rotation in the supine position were therefore made using both the digital goniometer and a universal goniometer.…”
Section: Methodsmentioning
confidence: 99%
“…Ainsi, le type d'application utilisée devrait être toujours le même pour limiter les risques d'erreurs inhérents à l'outil [11]. Les points de repère sur les patients doivent être strictement les mêmes, ainsi que la position choisie, pour limiter les erreurs liée aux physiothérapeutes [38,42]. Enfin les tests devraient être réalisés dans des conditions similaires pour les patients (environnement, heure, activités concomitantes, …) [8].…”
Section: Au Niveau De L'épaule Ce Sont éGalement Les Mesures D'abducunclassified